Pengaruh Promosi Instagram Terhadap Keputusan Berkunjung Wisatawan Ke Apar Mangrove Park Kota Pariaman - Serena Azni; Hijriyantomi Suyuthie (Lembaga Pengembangan Kinerja Dosen, 2024)
This research purpose is to analyze the effect of Instagram promotion on tourist visiting decisions to Apar Mangrove Park in Pariaman City. This research type is quantitative data survey research with an approach by causal associative. The research sample was taken with technique of Non Probability Sampling from tourists who have visited Apar Mangrove Park in Pariaman City as many as 325 respondents. The research results state that Instagram promotion is in the sufficient category have a percentage of 63.42%, and visiting decisions are in the category in good with a percentage of 70.09%. The hypothesis testing results in the simple linear regression test obtained a Sig value of 0.000 <0.05, then the Instagram promotion variable (X) has a significant effect on the visiting decision variable (Y). The result of the regression coefficient equation is 0.237 with a Sig value of 0.000 <0.05. So every increase in the unit of Instagram promotion will increase 0.237 units of visiting decisions. The R square value of 0.08 means that the Instagram promotion effect on visiting decisions is 8.8%, while the rest is influenced by other factors.